Educational Media in Japanese Language E-Learning: Teacher Selection/Preparation and Perception - Desak Made Sri Mardani; I Wayan Sadyana (JTP - Jurnal Teknologi Pendidikan, 2022)
Educational Media is a determining factor in achieving the success of the learning process, especially in e-learning. E-learning is something new for teachers in Indonesia, especially Japanese high school and vocational high school teachers in Bali. There may be problems arising in the preparation and use of educational media. Therefore, it is important to know how the teacher determines the media in Japanese e-learning and teachers' perceptions of the use of these media. To obtain answers to these questions, a purposive online survey was conducted, followed by descriptive analysis. The survey was conducted on 117 Japanese high school and vocational high school teachers in Bali. The determination of the online learning platform is based on the results of discussions between related parties in education, especially students and teachers. The selection of educational media (teaching material) is tailored to the needs of delivering materials and the student conditions. Regarding teachers' perceptions of the use of media, there are differences in terms of the criteria for the gender of the teacher and the hours of experience of the teacher. Meanwhile, in the education level criteria, there is no difference in the perception of the teacher.